I think I am getting better at this.

Differentiate the given function:

f(x) = 1/4*x^8 - 1/2 *x^6 - x + 2

f'(x) = 1/4(8x^7) - 1/2(6*x^5) - 1

f"(x) = 2(x^7) -3(x^5) -1

Printable View

- Jun 4th 2006, 07:00 PMbeckyDouble check please
I think I am getting better at this.

Differentiate the given function:

f(x) = 1/4*x^8 - 1/2 *x^6 - x + 2

f'(x) = 1/4(8x^7) - 1/2(6*x^5) - 1

f"(x) = 2(x^7) -3(x^5) -1 - Jun 4th 2006, 07:05 PMThePerfectHackerQuote:

Originally Posted by**becky**

$\displaystyle f''(x)=2x^7-3x^5-1$

You probably meant to write,

$\displaystyle f'(x)=2x^7-3x^5-1$.

That is the simplification of,

$\displaystyle 1/4(8x^7)-1/2(6x^5)-1$ - Jun 4th 2006, 07:09 PMbeckyOoops - just a typo
I meant to write:

f'(x)